Addressing the challenge of photovoltaic growth: Integrating multiple objectives towards sustainable green energy development. (May 2023) - Hermoso, Virgilio; Bota, Gerard; Brotons, Lluis; Morán-Ordóñez, Alejandra
Abstract: Photovoltaic production is growing globally thanks to climate change mitigation efforts. However, this growth is seldom planned which can lead to conflicts with other land uses, mostly agriculture and biodiversity conservation. There is, therefore, urgent need for adequate planning to minimise potential conflicts. We demonstrate how to identify priority areas for photovoltaic development to meet projected targets for 2050, as well as critical areas for the maintenance of different types of agriculture and biodiversity conservation, using Catalonia (NE Spain) as a case study. We tested three planning scenarios simulating alternative photovoltaic development models: setting targets at the whole regional scale or splitting those targets across counties distributing them equitably by county energy demand or area available for photovoltaic development. Photovoltaic targets could only be achieved when setting targets at the whole of Catalonia scale, although leading to heterogeneous distribution of development efforts and associated impacts on agriculture and biodiversity across counties. Setting targets for each county based on energy demand was far from achieving the regional photovoltaic development target, driven by the limited land available in some highly urbanised counties, where energy demand concentrates. On the other hand, setting targets based on area available within each led to the most equitable distribution of potential impacts of photovoltaic development, while also approaching the regional photovoltaic development target. Adequate planning of photovoltaic development will be key to ensure that photovoltaic development does not flourish at the expenses of other land uses, like maintenance of agricultural production or biodiversity. Highlights: Solar energy is rapidly growing without adequate planning. Unplanned growth can impact other sectors, mostly agriculture and biodiversity. There are trade-offs associate with different development models. Concentrating development is efficient but leads to higher impacts. Distributing development more equitably across the territory helps reduce impacts.